Exploring Technology Needs to Improve Mental Health Service Coordination - Jatnika, Ihsan; Kusumawaty, Ira; Yunike, Yunike; Indarti, Dina; Nugraha, Mara (International Journal Scientific and Professional, 2026)
Mental health services in Indonesia face significant challenges in coordination between agencies, including mental hospitals, community health centers (Puskesmas), and private institutions. Lack of data integration, limited communication, and low technology utilization hinder service effectiveness. This study aims to explore the need for technology to improve mental health service coordination and identify solutions that can address these challenges. Using a qualitative descriptive approach, the study involved healthcare workers from mental hospitals, community health centers, and private institutions in the provinces of South Sumatra, Lampung, and Jakarta. The results indicate that the implementation of a technology-based integrated information system, telemedicine applications, and intensive training for healthcare workers are key desired solutions. Furthermore, improving inter-agency communication and providing adequate technological infrastructure are also considered important. These findings align with health information systems theory and technology accessibility theory, which suggest that technology can improve coordination and access to services. Despite limitations in terms of sample size and perspective, this study provides important insights into the application of technology in mental health services in Indonesia and suggests solutions to improve the effectiveness of coordination within the mental health service system.